Women Entrepreneurship in India‎: A Bibliometric Study - Ramadugula, Mr. Aditya; Paruchuru , Dr. Manjushree; M.V, Dr. Suryanarayana; Kumar, Sunil; Raju, Indukuri Bangar (International Journal of Accounting and Economics Studies, 2026)
In this study, we provide a comprehensive bibliometric analysis of the scholarly literature on women's entrepreneurship in India ‎from 2020 to 2025 using Biblioshiny and advanced network visualization tools to map the evolving intellectual landscape and ‎how various external factors have transformed entrepreneurial opportunities for women across sectors in India as it navigates ‎rapid digital transformation, post-pandemic recovery efforts, and gender-inclusive policies such as Start-up India and MUDRA. ‎We collected data from two major academic databases, Web of Science and Scopus, to capture a comprehensive review of the ‎high-quality, peer-reviewed literature. The findings show key trends, emerging themes, and ongoing challenges, and ‎collaborative networks and co-citation patterns highlight the interdisciplinary nature of the research, focusing on key authors, ‎influential journals, and foundational studies that have continued to shape the discourse. This study identifies the key ‎achievements and gaps in the current research to provide insights into existing knowledge frameworks and to offer strategic ‎recommendations for future research and policy interventions to stakeholders, including academics, policymakers, and ‎practitioners, on how digital innovations and supportive infrastructure can transform women-led necessity-driven ventures into ‎opportunity-led enterprises and contribute to an inclusive and sustainable entrepreneurial ecosystem‎.
Keywords: Women Entrepreneurship; India; Digital Transformation; Bibliometric Analysis; Policy Initiatives; ‎Socio-Cultural Barriers; Entrepreneurial ecosystem